Relationship of Transformational Leadership, Organizational Learning and Organizational Performance - Mutahar, Amena Y.; Rasli, Amran Md; Al-Ghazali, Basheer M. (International Journal of Economics and Financial Issues, 2015)
Purpose of this study is to analyze the influence of transformational leadership on organizational performance through the dynamic capabilities of organizational learning in telecom sector of Kingdom of Saudi Arabia (KSA). Structural equation modeling was used to test the research hypotheses. The data was collected through survey questionnaires which were distributed to the employees of telecom sector of KSA. A random sample of 70 employees was used to collect the data. The response rate was 80%. The results reveal that transformational leadership positively influences the organizational performance and learning. The study also confirms existence of positive association between organizational learning and performance. The study is useful for the managers in telecom sector to understand the impact of transformation leaders to enhance learning capabilities of the employees which ultimately increases the performance of the employees in telecom sector. Keywords: Transformational Leadership, Organizational Learning, Organizational Performance JEL Classifications: D8; L25